1994
DOI: 10.1507/endocrj.41.supplement_s93
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of Placental Proteases: Interaction Between Pregnancy-Induced Bioactive Peptides and Proteases

Abstract: Abstract.We found 9 proteases in human placenta. Our studies showed that these placental proteases metabolize vasoactive and immunomodulating peptides, possibly derived from the fetus, and protect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The fetus is known to produce vasopressin (De Vane and Porter 1980) and angiotensin (Broughton Pipkin and Symonds 1977) and it has been reported that the increased vasopressinase (P-LAP) and angiotensinase (Aminopeptidase A, AP-A) activities of pregnancy serum may originate from placenta (Mizutani et al 1994a). It is also known that vasopressin and angiotensin are potent regulators of fetal blood pressure in normal and aberrant conditions (Reid 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The fetus is known to produce vasopressin (De Vane and Porter 1980) and angiotensin (Broughton Pipkin and Symonds 1977) and it has been reported that the increased vasopressinase (P-LAP) and angiotensinase (Aminopeptidase A, AP-A) activities of pregnancy serum may originate from placenta (Mizutani et al 1994a). It is also known that vasopressin and angiotensin are potent regulators of fetal blood pressure in normal and aberrant conditions (Reid 1992).…”
Section: Discussionmentioning
confidence: 99%
“…APN/CD13 is a type II 150-kDa membrane metalloprotease with an extracellularoriented catalytic domain. APN cleaves the N-terminal neutral residue of physiological peptides, and ubiquitously functions in various peptide metabolism pathways [45]. While DPPIV was detected in EECs, APN/CD13 was detected in ESCs and decidual cells [5].…”
Section: Apn/cd13 In Implantationmentioning
confidence: 99%
“…It is known that by constricting the umbilical artery and vein and the ductus arteriosus while dilating the pulmonary circulation, bradykinin (BK) is capable of mediating some of the rapid circulatory changes required of a neonate possibly under acute hypoxia [1]. As with other locally acting tissue hormones such as angiotensin II (ANG II) and oxytocin, the activity of BK is determined by factors leading to their degradation [2]. We reported that kininase I, kininase II (angiotensin converting enzyme, ACE) and endopeptidase 24.11 (CD10) appeared to be the most important in the degradation of BK in the placenta ± while ACE is located primarily in umbilical venous endothelial cells, CD10 is located in villous trophoblast [3 ± 6].…”
Section: Introductionmentioning
confidence: 99%